2003
DOI: 10.1136/thorax.58.4.311
|View full text |Cite
|
Sign up to set email alerts
|

T cell cytokine profiles in childhood asthma

Abstract: Background: An imbalance of T cell subsets in asthma with a predominance of Th2 type cells has been proposed. The aim of this study was simultaneously to detect surface markers and intracellular production of cytokines in T cells from the airways of children with and without asthma. Methods: Bronchoalveolar lavage (BAL) fluid was obtained by wedging a suction catheter into the distal airway immediately before elective surgery. Cells were stimulated with phorbol 12-myristrate 13-acetate (PMA) and ionomycin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 57 publications
2
51
0
2
Order By: Relevance
“…Increased eosinophil numbers in BALF of asthmatic subjects were not related to disease severity, whereas neutrophilic inflammation was often correlated with disease severity [36][37][38]. Increase in interferon-cproducing cells [39] and in interferon-c concentrations [40] were found in BALF of asthmatic children. Furthermore, young asthmatic children had increased activated macrophages that released pro-inflammatory mediators (e.g.…”
Section: Balfmentioning
confidence: 81%
“…Increased eosinophil numbers in BALF of asthmatic subjects were not related to disease severity, whereas neutrophilic inflammation was often correlated with disease severity [36][37][38]. Increase in interferon-cproducing cells [39] and in interferon-c concentrations [40] were found in BALF of asthmatic children. Furthermore, young asthmatic children had increased activated macrophages that released pro-inflammatory mediators (e.g.…”
Section: Balfmentioning
confidence: 81%
“…In humans, it has been shown that expression of IL-4 and its receptor correlates with asthma [24,25]. Furthermore, murine studies demonstrate a role for IL-4 in BAL and lung eosinophil accumulation [26,27], and mice deficient in IL-4 are not hyperreactive when sensitized and challenged to OVA [28].…”
Section: Discussionmentioning
confidence: 99%
“…It stimulates antigen presenting cells and major histocompatibility complex (MHC) class II molecule expression, driving specific immune responses through antigen recognition and antibody production. In the lung, IFN-␥ signaling has been implicated in viral infections, sarcoidosis, mycobacterial infections, cystic fibrosis, and hypersensitivity pneumonitis (8,(23)(24)(25)39). IFN-␥ may play a role as a modifier of cytokine/ chemokine production and may influence cellular recruitment into inflammatory lesions.…”
mentioning
confidence: 99%